Optimizing the Performance of the Sragen Police Traffic Unit Gakkum in Implementing Restorative Justice for Traffic Accident Law Enforcement - Alfare, Azis (Tanggon Kosala, 2024)
The problem of traffic accidents, especially at the Sragen Police, continues to increase from year to year. The number of traffic accidents at the Sragen Police Station is quite high in Central Java Province. In law enforcement Sragen Police often use Restorative Justice. There is a need to optimize the performance of the Satlantas Police Unit of the Sragen Police in implementing Restorative Justice so that it can provide benefits to reduce traffic accidents at the Sragen Police. The issues to be discussed are regarding the performance of the Sragen Police Satlantas Unit and the organizational resources of the Sragen Police Satlantas Unit in implementing Restorative Justice. In order to be able to answer this problem, a research was carried out in the Sragen Police area using management theory, Organizational Resources, and SWOT. There are several findings in the research that has been conducted that the performance of the Sragen Police Satlantas Unit in implementing Restorative Justice is still not optimal and the organizational resources of the Sragen Police Satlantas Unit in implementing Restorative Justice are still not optimal. In order to be able to provide solutions to existing problems, solutions to problems can be provided such as the need for optimization of planning, implementation and supervision by the Gakkum Unit and the need for optimization of the utilization of personnel, budgets, methods and facilities